Earthquake response of low-rise RC moment frame structures according to energy dissipation ratio of beam-column joints. Issue 1 (2nd January 2018) - Feng, Feifan; Jiang, Keyi; Hwang, Hyeon-Jong; Yi, Wei-Jian
Abstract: Seismic response of RC moment frame structures (particularly, in low-rise buildings) is affected by the inelastic hysteretic response and energy dissipation of beam-column joints. In current earthquake design codes, however, the earthquake response of the structures is evaluated without direct consideration of the energy dissipation of beam-column joints. In the present study, non-linear time history analysis using the energy-based hysteresis model was carried out to investigate the effect of the energy dissipation performances of the beam-column joints on the seismic response of the structures. To demonstrate the applicability of the proposed analysis method, it was applied to existing dynamic test results of RC moment frame structures. On the basis of the proposed method, non-linear time history analysis for six different typed low-rise RC moment frame structures under 14 earthquake records was performed. Design parameters were the energy dissipation ratios of beam-column joints (from pinching behavior to elasto-perfectly plastic behavior), moment frame stories (3, 5, and 9 stories), and moment frame configuration (two and four spans). The analysis results showed that the low energy dissipation of beam-column joints increased the ductility requirement of the low-rise RC moment frame structures.